Engaging high school students in systems biology through an e-internship program [version 1; referees: 2 approved] - Wim E Crusio; Cynthia Rubino; Anna Delprato (F1000Research, 2017)
In this article, we describe the design and implementation of an e-internship program that BioScience Project offers high school students over the summer. Project topics are in the areas of behavioral neuroscience and brain disorders. All research, teaching, and communication is done online using open access databases and webtools, a learning management system, and Google apps. Students conduct all aspects of a research project from formulating a question to collecting and analyzing the data, to presenting their results in the form of a scientific poster. Results from a pilot study indicate that students are capable of comprehending and successfully completing such a project, and benefit both intellectually and professionally from participating in the e-internship program.